Reductions in the prevalence and incidence of geohelminth infections following a city-wide sanitation program in a Brazilian Urban Centre. - Luciene Maura Mascarini-Serra; Carlos A Telles; Matildes S Prado; Sheila Alvim Mattos; Agostino Strina; Neuza M Alcantara-Neves; Mauricio L Barreto (Public Library of Science (PLoS), 2010)
In the city of Salvador, a large urban centre in Northeast Brazil, a city-wide sanitation intervention started in 1997, aimed at improving the sewerage coverage of households from 26% to 80%. Our aim was to study the impact of the intervention on the prevalence and incidence of geohelminths in the school-aged population.THE STUDY COMPRISED TWO COMPARABLE COHORTS: the first assembled in 1997, before the intervention, and the second assembled in 2003, after the intervention. Both were sampled from 24 sentinel areas chosen to represent the different environmental conditions throughout the city. Copro-parasitological examinations were carried out on every individual from both cohorts, at baseline and nine months later. Demographic, socio-economic, and environmental data were collected using semi-structured questionnaires and environmental surveys. A hierarchical modelling approach fitting a sequence of Poisson multivariate linear models was undertaken to test the effect of the intervention variables on the prevalence and incidence rate ratios.729 and 890 children aged 7-14 years (mean = 10.4 y, SD = 0.05 y) were analysed over the first and the second cohorts, respectively. The adjusted reductions of the prevalence and incidence rates at the second in relation to the first cohort were 27% and 34%, 25% and 32%, 33% and 26%, and 82% and 42% for geohelminths overall, Ascaris lumbricoides, Trichuris trichiura, and hookworm, respectively. Hierarchical modelling showed that a major part of each of these reductions was explained by the intervention.Our results show that a city-wide sanitation program may reduce significantly the prevalence and incidence of geohelminths.